CONSUMPTION PATTERNS OF SUGAR SWEETENED BEVERAGES IN THE UNITED STATES - Han, Euna (2013)
BACKGROUND: Few previous studies investigated consumption distributions of sugar sweetened beverages (SSBs) over time and individual-level associations despite recent interest in SSBs regarding obesity control. OBJECTIVE: To assess consumption patterns and individual-level associations. DESIGN: Trend and cross-sectional analyses of 24-hour dietary recall data and demographic characteristics and socioeconomic status (SES) drawn from the National Health and Nutrition Examination Survey (1999–2000, 2001–2002, 2003–2004, 2005–2006, and 2007–2008). PARTICIPANTS/SETTING: Children (2–11 years, N=8,627), adolescents (12–19 years, N=8,922), young adults (20–34 years, N=5,933), and middle-aged and elder adults (≥35 years, N=16,456). STATISTICAL ANALYSES PERFORMED: Age-stratified regression analyses for SSBs overall and by subtypes. RESULTS: The prevalence of heavy total SSB consumption (≥500 kcal/day) increased among children (4% to 5%) although it decreased among adolescents (22% to 16%) and young adults (29% to 20%). Soda was the most heavily-consumed SSB in all age groups except for children. Prevalence of soda consumption decreased, whereas heavy sports/energy drink consumption tripled (4% to 12%) among adolescents. Black children and adolescents showed a higher odds of heavy fruit drink consumption (OR=1.71 and 1.67) than whites. Low-income children had a higher odds of heavy total SSB consumption (OR=1.93) and higher caloric intake from total SSBs and fruit drinks (by 23 and 27 kcal/day) than high-income children. Adolescents with low- versus high-educated parents had a higher odds of heavy total SSB consumption (OR=1.28) and higher caloric intake from total SSBs and soda (by 27 and 21 kcal/day). Low- versus high-SES was associated with a higher odds of heavy consumption of total SSBs, soda, and fruit drinks among adults. CONCLUSIONS: Prevalence of soda consumption fell but non-traditional SSBs rose. Heterogeneity of heavy consumption by SSB types across racial/ethnic subpopulations and higher odds of heavy SSB consumption among low-SES populations should be considered in targeting policies to encourage healthful beverage consumption.